2022
DOI: 10.1097/cco.0000000000000893
|View full text |Cite
|
Sign up to set email alerts
|

Postneoadjuvant treatment for triple-negative breast cancer

Abstract: Purpose of reviewTriple-negative breast cancer (TNBC) has been conventionally associated with poor prognosis, as a result of limited therapeutic options. In the early setting, prognosis is informed by clinical–pathological factors; for patients receiving neoadjuvant treatments, pathological complete response (pCR) is the strongest factor. In this review, we mapped the landscape of clinical trials in the postneoadjuvant space, and identified three patterns of clinical trial design.Recent findingsFor patients at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…As olaparib is an important treatment option for TNBC patients who carry gBRCA1/2 mutations and do not achieve a pCR after neoadjuvant chemotherapy, even more patients might have been eligible for adjuvant olaparib if all patients had received neoadjuvant chemotherapy. Other treatment options are available for patients who do not achieve a pCR [25]: according to the CREATE-X trial, postneoadjuvant capecitabine improves OS in patents with TNBC [26]. Moreover, the KEYNOTE-522 trial found that patients without a pCR will also benefit from the checkpoint inhibitor pembrolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…As olaparib is an important treatment option for TNBC patients who carry gBRCA1/2 mutations and do not achieve a pCR after neoadjuvant chemotherapy, even more patients might have been eligible for adjuvant olaparib if all patients had received neoadjuvant chemotherapy. Other treatment options are available for patients who do not achieve a pCR [25]: according to the CREATE-X trial, postneoadjuvant capecitabine improves OS in patents with TNBC [26]. Moreover, the KEYNOTE-522 trial found that patients without a pCR will also benefit from the checkpoint inhibitor pembrolizumab.…”
Section: Discussionmentioning
confidence: 99%